Simulation of Batang Agam River Capabilities as Effect of LandUse Changes - Dalrino; Hartati; Suhendrik Hanwar; Ilham Eka Putra (International ABEC, 2022)
Batang Agam River is one of the rivers in West Sumatra Province that crosses Bukittinggi City, Agam Regency, Payakumbuh City and Limapuluh Kota Regency. The river is ± 60 Kilometers length with headwaters in Bukittinggi city and empties into Batang Sinamar in Limapuluh Kota Regency. With growth development of Bukit Tinggi, so that existing lands such as rice fields and other fields have changed functions into built-up land such as housing, offices, trade and so on. This resulted an increasement of surface runoff coefficient (coefficient C) and flow rate, which resulted in frequent flooding of Batang agam. These will induced flood, for example on 10 December 2018 flood which inundating SDN 18 Koto Tangah in Jorong Uba and 9 February 2020 flood which inundated 6 Hectare of rice fields in Kamang Hilia. To find out the magnitude of changes in land use and flood discharge that occurred in the Batang Agam watershed, a comparison of land use in 2011 with 2019 and flood discharge that occurred in 2011 with 2019. After calculating the results of the flood discharge calculation, the flood discharge was simulated using HEC-RAS software with a 5-year return period to get the overflowing water level and the area of the puddle. From the calculation results obtained an increase in the runoff coefficient value from 0.35 to 0.467, this resulted in a significant increase in flood discharge in each return period and the modeling carried out obtained the results of the maximum flood height reaching 3.13 m from the riverbed, this height is close to the flood height observed in the field, which is as high as 3.03 m.